The ankyrin repeat-containing protein Akr1p is required for the endocytosis of yeast pheromone receptors. - Givan, S A (1997)
The Saccharomyces cerevisiae a-factor receptor (Ste3p) requires its C-terminal cytoplasmic tail for endocytosis. Wild-type receptor is delivered to the cell surface via the secretory pathway but remains there only briefly before being internalized and delivered to the vacuole for degradation. Receptors lacking all or part of the cytoplasmic tail are not subject to this constitutive endocytosis. We used the cytoplasmic tail of Ste3p as bait in the two-hybrid system in an effort to identify other proteins involved in endocytosis. One protein identified was Akr1p, an ankyrin repeat-containing protein. We applied three criteria to demonstrate that Akr1p is involved in the constitutive endocytosis of Ste3p. First, when receptor synthesis is shut off, akr1 delta cells retain the ability to mate longer than do AKR1 cells. Second, Ste3p half-life is increased by greater than 5-fold in akr1 delta cells compared with AKR1 cells. Third, after a pulse of synthesis, newly synthesized receptor remains at the cell surface in akr1 delta mutants, whereas it is rapidly internalized in AKR1 cells. Specifically, in akr1 delta mutants, newly synthesized receptor is accessible to exogenous protease, and by indirect immunofluorescence, the receptor is located at the cell surface. akr1 delta cells are also defective for endocytosis of the alpha-factor receptor (Ste2p). Despite the block to constitutive endocytosis exhibited by akr1 delta cells, they are competent to carry out ligand-mediated endocytosis of Ste3p. In contrast, akr1 delta cells cannot carry out ligand-mediated endocytosis of Ste2p. We discuss the implications for Akr1p function in endocytosis and suggest a link to the regulation of ADP-ribosylation proteins (Arf proteins).